Priciples of molecular vironlogy - Cann, Alan J. (Elsevier academic press, 2005)
This book provides undergraduates with an excellent overview of molecular virology. This is an absolutely necessary book for students who have not been exposed to this topic and require a book that provides this information in a clear and concise manner. Updated editions are extremely important in such a rapidly changing field. New discoveries have been included in this edition which enables students to feel that they are receiving the latest information.